ANALYSIS OF THE AMOUNT OF MONEY SUPPLY AND BI 7-DAY REVERSE REPO RATE ON INFLATION RATE IN INDONESIA - Ulfah Setia Iswara (PT. Arsil Reka Engineering, 2023)
This study aims to analyze the amount in circulation and interest rates on inflation in Indonesia. Based on the source, the type of data in this study is secondary data, because the data collected is data in the form of numbers or numbers. The data used is quantitative data from January 2016 to December 2021 with this research conducted in Indonesia. This research is a qualitative descriptive study with a literature method through literature studies supported by secondary data obtained from Bank Indonesia and the Indonesian Central Bureau of Statistics. The results of this study explain that the money supply and interest rates affect the high and low inflation that occurs in Indonesia.